Analisis Penggunaan Prefiks Pe- pada Rubrik Surat Pembaca Harian Kompas sebagai Bahan Pembelajaran Bahasa Indonesia Siswa Kelas X SMK Muhammadiyah Delanggu. - Yuliastuti, Anggi; , Drs. Yakub Nasucha, M.Hum (2016)
Abstract Anggi Yuliastuti/A310120103. THE ANALYSIS OF USING PREFIXS PE- ON DAILY READERS LETTER SECTION KOMPAS EDITION IN DECEMBER 2015 AS A LEARNING MATERIAL INDONESIAN STUDENTS IN GRADE X SMK MUHAMMADIYAH DELANGGU. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan. Universitas Muhammadiyah Surakarta. Agustus, 2016. The study aims to: 1) to describe the using prefix pe- on daily readers letters section Kompas edition in December 2015 as a learning material Indonesian students at grade X SMK Muhammadiyah Delanggu. 2) to describe the function prefix pe- on daily readers letters section Kompas edition in December 2015 as a learning material Indonesian students at grade X SMK Muhammadiyah Delanggu. Type of this study is qualitative. The object of this research is using prefix pe- on daily readers letters section Kompas edition in December 2015. Data were collected through technic book, listening and writing. Dara werw analyzed using For Direct Element. The result of this study 1) using prefix pe- of rubric readers letter daily Kompas edition in December 2015 consist of five variation shape using, include pe-, pem-, pen-, peny-, and peng-. From 24 data that analyzed of using prefix pe- are 4 data, using prefix pe- morph pem- are 6 data, using prefix pe- morph pen- are 5 data, using prefix pe- morph peny- are 2 data, and using prefix pe- morph peng- are 7 data. (2) function prefix pe- of the rubric readers letter daily Kompas edition on December 2015 in general have function to forming noun base verb. This conclusion of this study are using prefix pe- included six variation shape, while function prefix pe- that more dominant is forming noun from base verb.